Development of a new understanding of the basic properties of evidence and other provisions of the procedure for dealing with them and their sources in criminal proceedings - Ланцедова, Юлія Олександрівна; Сіроченко, Тетяна Вячеславівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
In the article new edition of the norm CPC of Ukraine on the understanding of the essence of evidence and their basic legal properties, sources, subjects, order and exhaustive list of actions for their receipt and forms of operating such information in criminal proceedings is proposed. The essence of the evidence and of each their primary and additional basic legal properties is disclosed. The variant of the decision of a problem of subjects of reception of proofs and participation of other persons in the given procedure is offered. Outlined an exhaustive list of those receiving investigative and judicial actions, as well as forms of submission, evaluation and use of evidence in criminal proceedings.